Pengaruh Disiplin Kerja,Motivasi Intrinsik,Komitmen Dan Kompensasi Finansial Terhadap Kineja Karyawan Konveksi Agung Mandiri - Yesinta Priyastiani; Endah Kurniawati; Ririn Wahyu Arida (Politeknik Kampar, 2023)
Human resource performance is the relationship between output (goods or services) and input (labor, materials, money). Many things affect employee performance including motivation, work discipline and job satisfaction. Agung Mandiri Tulungagung Convection is a company in the garment sector that was established in 1998. Employee performance at Agung Mandiri Convection is based on the number of units/machines, besides that the presence of employees every day according to working hours. However, employee obedience to Agung Mandiri Convection was lacking, resulting in production delays. At the Agung Mandiri Convection there is a lack of discipline from employees towards the company in improving employee performance, as well as a lack of motivation, employee commitment, and compensation in the form of salaries and wages that do not match what employees expect. The purpose of this research is to explain the influence of work discipline, intrinsic motivation, commitment to financial compensation on the performance of employees of the Agung Mandiri convection company. This research is included in quantitative research and the sampling technique used is saturated sampling strategy, with a total of 35 employees participating. Sources of data in this study were primary data obtained by conducting direct interviews and distributing questionnaires to respondents and secondary data obtained through literature studies. The measurement scale used for each variable in this study is the Likert scale. The results of tests carried out using the simulatan test of work discipline, intrinsic motivation, commitment and financial compensation have an effect of 82.6% on employee performance. The results of this study simultaneously work discipline, intrinsic motivation, commitment and financial compensation have a positive and significant effect on the performance of Agung Mandiri convection employees.